Surface aspects of novel Bio-HEAs MAO-treated in a Ca-, P-, and Mg-rich electrolyte - Sousa, T. S.P. [UNESP]; Torrento, J. E.M. [UNESP]; Kuroda, P. A.B.; Gonçalves, V. R.M. [UNESP]; Coan, K. S. [UNESP]; Correa, D. R.N. [UNESP]; Grandini, C. R. [UNESP] (Elsevier, 2024)
This study evaluated the effect of alloying elements, applied voltage, and bioactive species (Ca, P, and Mg) enrichment during the micro-arc oxidation (MAO) treatment of novel high entropy alloys (HEAs) targeted for biomedical applications. The non-equiatomic TiZrNbTaMo (TaMo), TiZrNbTaMn (TaMn), and TiZrNbFeMo (FeMo) samples were submitted to MAO treatment at distinct voltages (100, 200, and 300 V), then their chemical, phase, and morphological aspects were evaluated by x-ray photoelectron spectroscopy (XPS), x-ray diffraction (XRD), and scanning and transmission electron microscopy (SEM and TEM). Finally, the preliminary physicochemical behavior regarding contact angle and surface energy in distilled water at room temperature was evaluated. The results indicated that the alloying elements played a global role in the bulk's phase composition, possessing distinct proportions of BCC and HCP phases. The MAO-treated surfaces depicted different mechanisms of anodic oxide growth and dielectric breakdown, forming the typical porous surface at distinct applied voltages. The bioactive species (Ca, P, and Mg) were gradually enriched in the oxide layer, composed of distinct nano-crystalline and amorphous layers that are typical of MAO-treated surfaces. As a result, roughness, contact angle and surface energy values of the MAO-treated samples were affected by the applied voltage and the bulk's chemical composition, indicating potential for use in the biomedical field, especially as long-term implants and bone fixation devices.
Keywords: Bioactive elements; Biomaterial; HEA; MAO; Voltage